Penyuluhan Pertanian Presisi Menggunakan Mesin Pencacah Dan Pelatihan Pembuatan Silase Pada Petani Cabai Di Desa Pulau Negara, Kabupaten Ogan Ilir - Supli Effendi Rahim; Mukhtarudin Muchsiri; Asvic Helida; Erni Hawayanti; Rusmila; Nia Fitria (Altifani Journal: International Journal of Community Engagement, 2026)
This community service activity aims to enhance the capacity of chili farmers in Pulau Negara Village through the implementation of precision agriculture technology and waste processing. The program focuses on the utilization of organic matter shredding machines and training in livestock feed silage production to address the low efficiency of crop waste management. This initiative involved 20 farmers and 5 extension agents, employing methods such as counseling, equipment demonstrations, practical training, and mentoring. The silage was produced using grass and chili plant residues, supplemented with bran, molasses, and EM4 through a two-week fermentation process. Evaluation using pre-test and post-test methods showed a significant increase in the participants' knowledge and skills. Understanding of precision agriculture increased from 30% to 85%, mastery of shredding machines rose from 20% to 90%, and silage-making proficiency improved from 15% to 88%. These results demonstrate the effectiveness of appropriate technology in fostering innovation and the integration of sustainable crop-livestock systems. These findings are expected to serve as a foundation for local governments in formulating farmer empowerment policies based on waste utilization and local technology.